Discussion about the stratigraphic range of "Pseudofurnishius murcianus" van den Boogaard (Conodonta) in the Iberian Peninsula, from the Calasparra section (Murcia, Spain) - Plasencia, P.; Márquez-Aliaga, A. (Journal of Iberian Geology, 2011)
The biostratigraphy of Calasparra Section is well-estabished with an ammonoid biozonation and ranges from Lower to Upper Ladinian. The continuous presence of Pseudofurnishius murcianus van den Boogaard, a characteristic conodont species of the Sephardic realm, along the section makes it one of the most important sections in the Iberian Peninsula for the study of the species. The first apparition of P. murcianus in the section corresponds with the first of Eoprotrachyceras curionii taxon, which is the principal marker for the base of the Ladinian stage in the GSSP of the Anisian-Ladinian boundary, and the age of the youngest conodonts, based on ammonoids (Epigonus Zone) is Lower Ladinian (upper Fassanian). This is similar to the range of P. murcianus in the Saharonim Formation in Israel, where its earliest appearance is also Early Fassanian (Curionii zone) age.